2018
DOI: 10.1080/08870446.2018.1432759
|View full text |Cite|
|
Sign up to set email alerts
|

Social comparisons in adults with type 2 diabetes: Patients’ reasons for target selection

Abstract: Patients' reasons for a particular comparison are associated with short-term changes in affect and self-care motivation, and warrant greater empirical and clinical attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…The results are in line with the Identi cation/Contrast Model of comparison 15 that proposes that a downward comparison with greater identi cation leads to worse quality of life and less motivation, whereas identi cation with an upward standard increases quality of life and motivation. In our study, we found that ICD + patients identi ed more strongly with the worse-off standards in line with results from 42 and selected standards with bad coping more often.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results are in line with the Identi cation/Contrast Model of comparison 15 that proposes that a downward comparison with greater identi cation leads to worse quality of life and less motivation, whereas identi cation with an upward standard increases quality of life and motivation. In our study, we found that ICD + patients identi ed more strongly with the worse-off standards in line with results from 42 and selected standards with bad coping more often.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, despite comparable mood levels at the beginning of the study, ICD + patients displayed signi cantly worsened mood after presentation of the case vignette than ICD-patients, irrespective of their comparison choice (H4). 42 reported that patients with a more severe course of a type 2 diabetes had worse quality of life and higher levels of depression. In comparison, we only found trends towards worse psychological health in ICD + patients who also have a physically more severe disease in comparison to ICD-patients (H1).…”
Section: Discussionmentioning
confidence: 99%
“…Which combinations lead to the greatest increases in PA (or lead to increases vs decreases) and for whom are significant empirical questions [25,66,67]. Basic research indicates that the opportunity to select a comparison target does not always lead to optimal affective or health-relevant outcomes, nor does it always fulfill comparers' goals (eg, to feel better) [18,68,69]. Thus, providing information about only the targets that a PA app user wants may not lead to benefits.…”
Section: Social Comparison Theory and Evidence Relevant To Physical A...mentioning
confidence: 99%
“…One is that people do not always select the comparison opportunities that fulfill either self-improvement or self-enhancement goals; at times, their intentions are to confirm that their own situation is bad or could worsen or to justify not making difficult behavior changes such as increasing their PA (eg, "I'm already doing better than someone else, so I'm doing fine" [56,57]). Even when they do have positive, goal-oriented intentions for selecting particular comparison opportunities (eg, to learn important information or to feel better), their expectations are not always met by the target provided [58]. In such situations, the comparison opportunity may actually lead to negative outcomes.…”
Section: Xsl • Fomentioning
confidence: 99%